2021
DOI: 10.1007/s12117-021-09442-x
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and child criminal exploitation in the UK: implications of the pandemic for county lines

Abstract: In March 2020, the UK was placed in lockdown following the spread of the Covid-19 virus. Just as legitimate workplaces made changes to enable their employees to work from home, the illicit drugs trade also made alternative arrangements, adapting its supply models to ensure continuity of operations. Based upon qualitative interviews with 46 practitioners, this paper assesses how front-line professionals have experienced and perceived the impact of Covid-19 on child criminal exploitation and County Lines drug su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…At the dialogue event, there were reports that some forms of child exploitation had migrated online (The Rights Lab, 2021a). The latter reflects research on child victims of criminal exploitation during Covid-19 that found young people faced heightened risks of exploitation via social media (Brewster et al, 2021). What follows is an overview of policy responses captured in the evidence review in relation to the risks facing children living in the UK of entering exploitation.…”
Section: Children At Heightened Risk Of Exploitationmentioning
confidence: 98%
See 2 more Smart Citations
“…At the dialogue event, there were reports that some forms of child exploitation had migrated online (The Rights Lab, 2021a). The latter reflects research on child victims of criminal exploitation during Covid-19 that found young people faced heightened risks of exploitation via social media (Brewster et al, 2021). What follows is an overview of policy responses captured in the evidence review in relation to the risks facing children living in the UK of entering exploitation.…”
Section: Children At Heightened Risk Of Exploitationmentioning
confidence: 98%
“…Whilst studies have reported the impact of the pandemic on marginalised children around the world, few have focused specifically on children affected by modern slavery either as the children of those who have exited situations of slavery, child victims of exploitation or those at risk of entering exploitation. Research has been undertaken in relation to the implications of the crisis for child criminal exploitation in the UK (Brewster et al, 2021 ; Pitts, 2020 ; Racher & Brodie, 2020 ). This emerging research indicates that the safeguarding ability of organisations in England was hindered by the Covid‐19 restrictions especially, the reduction in face‐to‐face contact with young people exploited for County Lines purposes (Brewster et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The noticeable exceptions were drug offences and domestic violence. 31 A study by Brewster et al 31 outlines the impact that Covid-19 had on the county lines model and how adaptations had to be made during the lockdown periods. There had been some overall indication that the pandemic had been an inhibitor of crime 31 but due to the lack of evidence and studies prior to Covid-19, the impact can only be assessed through media representation and the opinions of experts in the field.…”
Section: Recorded Drug Offencesmentioning
confidence: 99%
“…In the UK the illicit drugs market is estimated to be worth around £9.4 billion per year and drug poisoning deaths are currently at record levels. 2 4400 deaths in England and Wales were recorded due to drug misuse in 2019 according to the Office of National Statistics, increasing to 4561 deaths in 2020, 60.9% higher than a decade earlier in 2010. Opiates, such as heroin and morphine, accounted for just under half, 49.6%, of overdoses in England and Wales.…”
Section: Introductionmentioning
confidence: 99%